Assessment of interpersonal anxiety in stutters - Ilic Savic, Ivana; Petrović-Lazić, Mirjana (Psihološka istraživanja, 2021)
Stuttering is defined as a speech disorder characterized by involuntary repetitions and prolongations of speech elements, i.e. voices, syllables or words. The evaluation of interpersonal anxiety in stuttering pathology should indicate and encourage a new perspective, to provide a conceptual approach that has the potential to better understand the affective field of a stuttering person by completing a guide to stuttering rehabilitation. The aim of this study was to compare the degree of interpersonal anxiety of stuttering subjects in both typical populations and the potential effect of age differences and different forms of stuttering on the degree of interpersonal anxiety. The sample included 48 subjects, 24 stuttering subjects and 24 non-stuttering subjects. The assessment of interpersonal anxiety was performed using the WILLOUGHBY questionnaire to assess the degree of interpersonal anxiety. The obtained results show that the subjects who stutter are more anxious than the subjects of the typical population [F(1, 44) = 13.66, p < .01]. Stuttering subjects, older age groups showed a higher degree of interpersonal anxiety compared to younger subjects [F(1, 22) = 8.544, p
Keywords: interpersonal anxiety, stuttering, rehabilitation